2019
DOI: 10.1016/j.scs.2019.101481
|View full text |Cite
|
Sign up to set email alerts
|

Demand response events in district heating: Results from field tests in a university building

Abstract: Demand side management will play a major role in future energy systems. However, while they have been explored in some depth for electricity grids, a similar progress has not been made for district heating networks (DHN). To this end, the current work field-tested the effect of demand side management, in the form of price based, demand response (DR) events, in the DHN catering to a university building. Responding to variations in a pricing model, the temperature of inlet water was varied from the heating water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…This depends on the structure of the hydronic system. Mishra et al (2019) studied the effect of centralised control on room air temperature in a similar office building as presented in Publication I and Publication II and found that variations in the circulating water temperature can be measured with a short time-lag after in the rooms. However, load shifting at the substation also should be timed in a manner that it benefits the heat supplier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This depends on the structure of the hydronic system. Mishra et al (2019) studied the effect of centralised control on room air temperature in a similar office building as presented in Publication I and Publication II and found that variations in the circulating water temperature can be measured with a short time-lag after in the rooms. However, load shifting at the substation also should be timed in a manner that it benefits the heat supplier.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, differences in building components, occupant patterns and other unpredictable conditions related to buildings could affect indoor conditions in a way that is challenging to model accurately. On the implementation side, studies with limited floor area in a building, such as Mishra et al (2019) as well as Publication I and II. Field studies with a limited number of buildings, including work from Wernstedt et al (2007), Österlind (1982), Kensby et al (2015), Sweetnam et al (2019), Kärkkäinen et al (2003) and Publication IV are commonly exploited for validating those strategies.…”
Section: Demand Response In Buildingsmentioning
confidence: 99%
“…Campus level interactions with both the water network and the district heating network shows potential in heating load flexibility. In a price induced demand response scheme for a district heating network in a university campus, substations participated by changing their inlet water temperature while monitoring the occupant's thermal comfort [121].…”
Section: Urban District Contextmentioning
confidence: 99%
“…Dynamic pricing is considered to be the most efficient pricing program to combine with the demand response (Hu et al, 2015). Mishra et al, (2019) demonstrated the effects of centralized demand response control of district heating on indoor thermal conditions and 4 perceived thermal comfort by using field tests in a university building. Thus, the performance of demand response on buildings can be improved with smart control strategies.…”
Section: Introductionmentioning
confidence: 99%